Low-dose anti-thymocyte globulin plus low-dose post-transplant cyclophosphamide-based regimen for prevention of graft-versus-host disease after haploidentical peripheral blood stem cell transplants: a large sample, long-term follow-up retrospective study - Li, Xingying; Yang, Jun; Cai, Yu; Huang, Chongmei; Xu, Xiaowei; Qiu, Huiying; Niu, Jiahua; Zhou, Kun; Zhang, Ying; Xia, Xinxin; Wei, Yu; Shen, Chang; et al. (Frontiers in Immunology, 2023)
The novel low-dose anti-thymocyte (ATG, 5 mg/kg) plus low-dose post-transplant cyclophosphamide (PTCy, 50 mg/kg) (low-dose ATG/PTCy)-based regimen had promising activity for prevention of graft-versus-host disease (GVHD) in haploidentical-peripheral blood stem cell transplantation (haplo-PBSCT), but its impacts on long-term outcomes remain to be defined. Now, we performed a large sample, long-term follow-up retrospective study to evaluate its efficacy for GVHD prophylaxis. The study enrolled 260 patients, including 162 with myeloid malignancies and This is a provisional file, not the final typeset article 98 with lymphoid malignancies. The median follow-up time was 27.0 months. For the entire cohort, the cumulative incidences (CIs) of grade Ⅱ-Ⅳ and Ⅲ-Ⅳ acute GVHD (aGVHD) by 180 days were 13.46% (95% CI, 9.64%-17.92%) and 5.77% (95% CI, 3.37%-9.07%); while total and moderate/severe chronic GVHD (cGVHD) by 2 years were 30.97% (95% CI, 25.43%-36.66%) and 18.08% (95% CI, 13.68%-22.98%), respectively. The 2-year overall survival (OS), relapse-free survival (RFS), GVHD-free, relapse-free survival (GRFS), non-relapse mortality (NRM), and CIs of relapse were 60.7% (95% CI, 54.8%-67.10%), 58.1% (95% CI, 52.2%-64.5%), 50.6% (95% CI, 44.8-57.1%), 23.04% (95% CI, 18.06%-28.40%) and 18.09% (95% CI, 14.33%-23.97%, respectively.The 1-year CIs of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) reactivation were 43.46% (95% CI, 37.39%-49.37%) and 18.08% (95% CI, 13.68%-22.98%), respectively. In multivariate analysis, the disease status at transplantation was associated with inferior survivor outcomes for all patients, myeloid and lymphoid malignancies, while cGVHD with superior outcomes for all patients and myeloid malignancies, but not for lymphoid malignancies. The results demonstrated that the novel regimen could effectively prevent the occurrence of aGVHD in haplo-PBSCT.